2021
DOI: 10.9770/jesi.2021.8.4(33)
|View full text |Cite
|
Sign up to set email alerts
|

Employment of foreign students after graduation in Hungary in the context of entrepreneurship and sustainability

Abstract: In recent decades, more and more international students, including paid and scholarship-funded students coming to study in Hungary, most of them are studying in higher education institutions. The experience of studying abroad has not only broadened foreign students' horizons, but also increased their entrepreneurial awareness to a certain extent, especially increased the number of foreign companies or businesses set up by foreign students to trade and cooperate with the host country. In this sense, they are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For a company to be sustainable, innovation and risk concerns must be taken into consideration [29]. Sustainable businesses emphasize the importance of entrepreneurial activity in achieving long-term social and environmental benefits [30]. Ecological degradation can be solved through business.…”
Section: Sustainable Entrepreneurship and Sustainable Entrepreneurial...mentioning
confidence: 99%
“…For a company to be sustainable, innovation and risk concerns must be taken into consideration [29]. Sustainable businesses emphasize the importance of entrepreneurial activity in achieving long-term social and environmental benefits [30]. Ecological degradation can be solved through business.…”
Section: Sustainable Entrepreneurship and Sustainable Entrepreneurial...mentioning
confidence: 99%
“…Based on prior findings, the literature endorses the fact that the entrepreneurship related education and/or trainings/workshops attended by the individuals influenced them to take entrepreneurial initiatives, as this education or training not only boosted their confidence, but also developed the required business-oriented skills [35]. Betáková et al [36] found that the intervention of educational institutions through entrepreneurial education helps students to develop and master entrepreneurial skills and apply those skills and learning in a practical field.…”
Section: Course In Entrepreneurshipmentioning
confidence: 99%
“…Here, entrepreneurship is treated as a significant solution to environmental degradation. In this way, entrepreneurship embraces the corporate social responsibility (CSR) to resolve environmental problems [35]. Environmental pollution can be reduced through entrepreneurial activities to support and promote the ecosystem [36].…”
Section: Sustainable Entrepreneurshipmentioning
confidence: 99%
“…Models that emphasize the importance of contingencies also highlight the limitations of rational career decision-making (Mitchell et al, 1999). These models claim that to varying degrees (Betáková et al, 2021;Betsworth & Hansen, 1996;Hart et al, 1971;Kakar et al, 2021;Williams et al, 1998), random events have an impact on people's career choices. As a result, some models, such as the "integrated career decision model," question whether fully rational career decisions are even possible.…”
Section: Decision Theories From the Perspective Of Career Choicementioning
confidence: 99%